Estimasi Model Hidrolika Menggunakan HEC-RAS 1-D dan Tren Prediksi Strategi Mitigasi Banjir - Rian Mantasa Salve Prastica; Asvira Ditya Siswanto (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2022)
Engineering modeling is becoming a trend and important because it can simulate a variety of decision scenarios to be applied in the field. With limited facilities and technology, 1-D modeling in hydraulics for flood mitigation is still a trend today. What are the weaknesses of this model and how is the prediction of future modeling trends? This study analyzes the flood modeling of the Tuntang River with the 1-D model using HEC-RAS to analyze the condition of the existing water level profile and flood mitigation scenarios with normalization. The results of the analysis show that the 1-D model can describe conditions in the field and scenarios clearly. However, the 1-D model has limitations because it cannot carry out simulations that consider aspects of construction costs, time, and budget allocation of stakeholders to determine the priority scale of disaster-affected areas. It requires a vulnerability analysis with field observations, 2-D or 3-D modeling, and the application of value engineering to optimize flood control strategies. With the advancement of technology, this trend is predicted to be something that will be done in the future.